A STUDY ON BANANA CULTIVATORS IN THOOTHUKUDI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Banana is the most widely consumed fruit, and is an attractive perennial fruit crop for small farmers. This is due to its high economic gains throughout the year compared to other crops like rice and wheat. Apart from the imputed value of family effort, the other effects like cost of production, on the whole income etc., are not favorable to the small farmers. Their agricultural lands depend on torrential rains. The greater parts of the lands are rain-fed areas. If the monsoon fails, then the farmers will be in hitch. In these circumstances, the government should shore up the agriculturists by granting financial assistance. Different strategies should be adopted to reduce the losses taking place out of high humid content of the banana. The banana is also fatally affected by some ailment. Therefore, an enduring research station may be elevated to protect the banana from various syndromes. By examining various research results as one; the government generates awareness among the farmers concerning banana cultivation and may push more farmers to cultivate this precious food, which is greatly vital in our habitual diet system. Among 29 districts of Tamil Nadu, Thoothukudi district ranks first in exporting banana. So Thoothukudi district is selected for the present study